Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

why underroot -a multiply by underroot -b is not equal ounderroot ab.

why underroot -a multiply by underroot -b is not equal ounderroot ab.

Grade:12th pass

1 Answers

Rinkoo Gupta
askIITians Faculty 80 Points
7 years ago
sqrt(-a)=sqrt(-1)sqrt(a)=isqrt(a)
sqrt(-b)=sqrt(-1).sqrt(b)=isqrt(b)
sqrt(-a).sqrt(-b)=(ia).(ib)=i^2.ab= -ab
Thanks & Regards
Rinkoo Gupta
AskIITians Faculty

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free